Literature Review of Frost Formation Phenomena on Domestic Refrigerators Evaporators - Daria Krasota; Przemysław Błasiak; Piotr Kolasiński (Energies, 2023)
The topic of frost formation on the heat exchanger surface has been gaining interest since the late 1940s. Scientists and industrial engineers from many scientific and R&D units around the world have been trying to understand the nature of frosting and implement solutions to prevent such an unwanted phenomenon from having a significant impact on the performance of heat exchangers (such as a decrease in heat transfer efficiency, mechanical damage, and condensation risk). The aim of this article is to summarize the present state of knowledge dedicated to frost formation types and morphology, review, and discuss the most recent studies relevant to the challenge of frost formation, focusing on the evaporator of the domestic refrigerator. The different types of domestic refrigerators are summarized, as are the different types of evaporators inside them. Common methods of testing frost formation phenomena on the evaporator are revisited in this article, and the analysis of the most recent mathematical models is presented as well. The input and output parameters of these models are grouped, and a similar analysis is conducted for the CFD models.